Inhibition of FvMYB10 transcriptional activity promotes color loss in strawberry fruit. (September 2020) - Chen, Guanqun; Xu, Pengbo; Pan, Jian; Li, Yang; Zhou, Junhui; Kuang, Huiyun; Lian, Hongli
Highlights: Mutation-FvMYB10 abolished to biosynthesize anthocyanin in Arabidopsis and strawberry. FvMYB10 localized as speckles, while FvmMYB10 was not. FvMYB10 directly bound and activated the expression of FvCHS2 and FvDFR1 . FvmMYB10 failed to bind and activate the expression of FvCHS2 and FvDFR1 . Abstract: FvMYB10 protein has been proved to be a transcriptional switch for anthocyanin biosynthesis in strawberry. A single nucleotide mutation in R2 domain of FvMYB10, named as FvmMYB10, is found to be responsible for the white color in strawberry variety 'Yellow Wonder'. However, the mechanism of FvmMYB10 suppresses anthocyanin biosynthesis in strawberry is largely unknown. Here, we show that the transcriptional level of FvMYB10 and key enzyme genes involved in anthocyanin biosynthesis in 'Yellow Wonder' were lower than that in red color variety 'Ruegen', especially at turning to ripening stage. The low expression level of FvmMYB10 may due to his inability to bind to its promoter region and activate its own expression. We found FvMYB10- overexpressing, but not FvmMYB10 -overexpressing, promote anthocyanin accumulation in Arabidopsis and strawberry fruit despite of their similar expression levels. In addition, subcellular localization assay indicated that FvMYB10-YFP, but not FvmMYB10-YFP, localized to sub-nucleus foci (speckles) in the nucleus, implying the mutation of FvMYB10 might inhibit its transcription factor activity and eventually interfere with its function. Subsequently, we confirmed that FvMYB10 bind to the promoter region of some specific key enzyme genes, including FvCHS2 and FvDFR1 and activated their expression. While FvmMYB10 failed to binding and transcriptional activating these genes. Our findings provide insights into molecular mechanism of anthocyanin biosynthesis regulated by MYB10 in strawberry fruits.